Critical theory, authoritarianism, and the politics of lipstick from the Weimar Republic to the contemporary Middle East. (December 2018) - Afary, Janet; Friedland, Roger
In 2012–13, we signed up for Facebook in seven Middle East and North Africa (MENA) countries and used Facebook advertisements to encourage young people to participate in our survey. Nearly 18, 000 individuals responded. Some of the questions in our survey dealing with attitudes about women's work and cosmetics were adopted from a survey conducted by the Frankfurt School in 1929 in Germany. The German survey had shown that a great number of men, irrespective of their political affiliation harbored highly authoritarian attitudes toward women and that one sign of authoritarianism was men's attitude toward cosmetics and women's employment. We wanted to know if the same was true of the contemporary MENA. Our results suggest that lipstick and makeups as well as women's employment are not just vehicles for sexual objectification of women. In much of MENA world a married woman's desire to work outside the house, and her pursuit of the accoutrement of beauty and sexual attractiveness, are forms of gender politics, of women's empowerment, but also of antiauthoritarianism and liberal politics. Our results also suggest that piety among Muslims per se is not an indicator of authoritarianism and that there is a marked gender difference in authoritarianism. Women, it seems, are living a different Islam than men.